Deep metagenomic characterization of gut microbial community and function in preeclampsia - Lv, Li-Juan; Li, Sheng-Hui; Wen, Ji-Ying; Wang, Guang-Yang; Li, Hui; He, Tian-Wen; Lv, Qing-Bo; Xiao, Man-Chun; Duan, Hong-Li; Chen, Min-Chai; Yi, Zhou-Ting; Yan, Qiu-Long; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Preeclampsia is a pregnancy complication characterized by severe hypertension and multiple organ damage. Gut microbiota has been reported to be involved in preeclampsia by the imprecise 16S rRNA amplicon technology. To resolve the preeclampsia gut microbiota deeper and more accurately, we performed shotgun metagenomic sequencing on the fecal samples from 40 early-onset preeclampsia and 37 healthy pregnant women. We recovered 1,750 metagenome-assembled genomes (representing 406 species) from the metagenomic dataset and profiled them abundances. We found that PE gut m icrobiota had enriched in some species belonging to Blautia, Pauljensenia, Ruminococcus, and Collinsella and microbial functions such as the bacitracin/lantibiotics transport system, maltooligosaccharide transport system, multidrug efflux pump, and rhamnose transport system. Conversely, the gut microbiome of healthy pregnant women had enriched in species of Bacteroides and Phocaeicola and microbial functions including the porphyrin and chlorophyll metabolism, pyridoxal−P biosynthesis, riboflavin metabolism, and folate biosynthesis pathway. PE diagnostic potential of gut microbial biomarkers was developed using both species and function profile data. These results will help to explore the relationships between gut bacteria and PE, and provide new insights in PE early warning.